2017
DOI: 10.1002/dc.23831
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pediatric neuroblastoma by urine cytology: A case report

Abstract: Neuroblastomas are embryonal tumors arising from the neuronal crest cells of the synaptic nervous system. Findings from aspiration cytology have been reported, but there have been no reports of urine cytology findings. Here, we report a case of pediatric neuroblastoma characterized by urine cytology. A 2-year-old boy presented with abdominal pain, nausea, and loss of appetite. Computed tomography revealed a large tumor in the left suprarenal region with massive infiltration into the kidney. Urinary cytology sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The symptoms of this disease are abdominal distension, abdominal pain, vomiting, anorexia, weight loss, fatigue, and so on. Although there are currently many therapeutic schemes for neuroblastoma such as surgical resection, radiotherapy, and chemotherapy, the survival rate of children is still low, so it poses a serious threat to the health of infants [3][4][5][6][7][8] . It has been found that clinical drugs used for treating other tumors may play a role in the treatment of neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of this disease are abdominal distension, abdominal pain, vomiting, anorexia, weight loss, fatigue, and so on. Although there are currently many therapeutic schemes for neuroblastoma such as surgical resection, radiotherapy, and chemotherapy, the survival rate of children is still low, so it poses a serious threat to the health of infants [3][4][5][6][7][8] . It has been found that clinical drugs used for treating other tumors may play a role in the treatment of neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%